Pentingnya Pendidikan Pancasila Dalam Pembentukan Identitas Kewarganegaraan - Raudhatul Fitriyah; Miskah Miskah; Oman Farhurohman (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Pancasila education plays a crucial role in shaping a strong and robust sense of citizenship identity. This article discusses the urgency and positive impact of implementing Pancasila education in the context of fostering citizenship identity in Indonesia. Through theoretical approaches and practical analyses, this article highlights the contribution of Pancasila education in imparting fundamental values such as justice, unity, and mutual cooperation to the younger generation. Pancasila education not only teaches knowledge about the basic concepts of the state but also fosters a sense of nationalism and love for the homeland. By strengthening citizenship identity, society becomes more aware of its rights and obligations as members of the nation, and is ready to actively participate in nation-building. This article also summarizes several effective strategies in implementing Pancasila education at various educational levels to enhance the understanding and awareness of citizenship among the younger generation.